P1857SALT CONSUMPTION, LIFESTYLE AND PROTEINURIA IN A HETEROGENEOUS YOUNG POPULATION. (6th June 2020) - Zullo, Claudia; Dallari, Lorenzo; Bagalà, Alfredo; Somma, Chiara; Ferro, Giuseppe; Burgio, Lorenzo; Dattolo, Pietro
Abstract: Background and Aims: Obesity, hypertension, smoke, high dietary salt intake and physical inactivity are the main modifiable risk factors for chronic kidney disease, that affects about 9-10% of Italian people. About daily salt intake, the World Health Organization recommends a maximum consumption of 5 grams of salt per day. In Italy, most people consume too much salt – on average 8-10 grams per day or around twice the recommended maximum level of intake. Aim of this study was to investigate dietary habits and lifestyle of the heterogeneous students population of "Scuola Carabinieri di Firenze" (attended by people coming from all Italian regions) and their relations with urinary abnormalities. Method: from November 2018 to March 2019 we collected anamnestic and anthropometric data, blood pressure measurements and body cellular mass (BCM) of 257 young subjects (152 males, 105 females; mean age 32 + 11 yy). We determinated sodium, chlorine and protein excretion on a spot urine sample in addition to plasma creatinine levels. Statistical analyses were performed using SPSS. Results: We analyzed preliminary data of urinary sodium excretion (UNa ), proteinuria (Up ) and hematuria (Urbc ) of all the subjects. Fifty-five percent of them had a UNa higher than 100 mmol/L (approximately equivalent to a dietary salt intake of 6 grams/day). In these subjects with higher salt consumption, Up and Urbc, measured by urine dipstick, were detectable in 32% and 21% respectively. In subjects with lower salt intake (less than 6 grams/day), Up and Urbc were 0% and 5% respectively. To determine if there was an association between our variables, we used Pearson correlation coefficient. We found that UNa was directly related to Up (r 0.26, p 0.002), age (r 0.22 p 0.011) and diastolic blood pressure (DBP, r 0.22, p 0.012). We also found that poor exercise (r -0.15, p 0.7) and low lean body mass percentage (r -0.15, p 0.7) were inversely related to UNa . Conclusion: high dietary salt intake is associated with elevated blood pressure and proteinuria in a young and "healthy" population. Hypertension and proteinuria are both known risk factors for the development of chronic kidney disease. Wrong dietary habits and lifestyles must be detected and corrected in order to prevent nephropathy onset.